ANALISIS YURIDIS FAKTOR PENGHAMBAT EKSEKUSI JAMINAN FIDUSIA DALAM MELINDUNGIKREDITUR (STUDIPADA PT. BANK M ANDIRI (PERSERO), Tbk BALAIKOTA MEDAN) - MELYSA NATALIA Y.TOBING (PREMISE LAW JURNAL, 2014)
ABSTRACT Credit contract with nonconforming credit can be an obstacle in conducting an execution on a fiduciary collateral object. Some retarding factors which impede an execution on fiduciary collateral object are the decrease of the value of fiduciary collateral object or the delay in paying the employees' wages. The contract of fiduciary collateral object has to be made in a Fiduciary Collateral Deed and registered to Fiduciary Board Office by a Notary, This is one of the legal protections for the Bank as the creditor when the debtor undergoes nonconforming credit. On this occasion, for the sake of security and for avoiding retarding factors in executing the fiduciary collateral object, the Bank needs to perform regular assessment on the fiduciary collateral object and on the debtor's business value, and assign Proxy Letter of Sale on fiduciary collateral object which has been bound as the collateral so that when nonconforming occur, the creditor can execute directly the fiduciary collateral object. Keywords: Execution, Fiduciary Collateral, Creditor